+0  
 
0
29
1
avatar

f(x) = 2x^2 - kx^2 + 4x + 5k - 2.

 

One root is the reciprocal of the other. Find the roots.

 Apr 28, 2022
 #1
avatar+122385 
+1

(2 - k)x ^2  +  4x  +  (5k   - 2)

 

Call the roots  m  and 1/m

 

The product of the roots  =   (5k - 2)  / (2 - k)

 

So

 

m * ( 1 /m)  =  (5k - 2)  / (2 - k)

 

       1  =   (5k - 2)  / (2 - k)

 

(2- k)  = ( 5k - 2)

 

4  = 6k

 

k = 4 / 6  =  2 / 3

 

So

 

(2 - k)x^2  + 4x  + (5k - 2)    = 0

 

(2 - 2/3)x^2  + 4x + (5 *(2/3) - 2)  = 0

 

(4/3)x^2 + 4x + 4/3  = 0

 

4x^2  + 12x  + 4       = 0  

 

4 ( x^2  + 3x + 1)  = 0

 

x^2  + 3x + 1  =  0

 

x^2  + 3x  =  -1

 

x^2  + 3x + 9/4  =  -1  + 9/4

 

(x + 3/2)^2  = 5/4

 

x + 3/2  = sqrt (5) / 2

 

x =   [sqrt (5)  -  3 ]   / 2  =  m

 

And    

 

1/ m  =    2 / [sqrt (5) - 3]

 

cool cool cool

 Apr 28, 2022
edited by CPhill  Apr 28, 2022

32 Online Users